Improving access to medicines via the Health Impact Fund in India: a stakeholder analysis. Issue 1 (1st January 2018) - McMullan, Patrick; Ajay, Vamadevan S.; Srinivas, Ravi; Bhalla, Sandeep; Prabhakaran, Dorairaj; Banerjee, Amitava
ABSTRACT: Background : In India, 50–65% of the population face difficulties in accessing medicines. The Health Impact Fund (HIF) is a novel proposal whereby pharmaceutical companies would be paid based on the measured global health impact of their drugs. We conducted a key stakeholder analysis to explore access to medicines in India, acceptability of the HIF and potential barriers and facilitators at policy level. Objectives : To conduct a stakeholder analysis of the HIF in India: to determine key stakeholder views regarding access to medicines in India; to evaluate acceptability of the HIF; and to assess potential barriers and facilitators to the HIF as a policy. Methods : In New Delhi, we conducted semi-structured interviews. There was purposive recruitment of participants with snowball sampling. Transcribed data were analysed using stakeholder analysis frameworks and directed content analysis. Results : Participation rate was 29% (14/49). 14 semi-structured interviews were conducted among stakeholders in New Delhi. All participants highlighted access to medicines as a problem in India. There were mixed views about the HIF in terms of relevance and scaleability. Stakeholders felt it should focus on diseases with limited or no market and potentially incorporate direct investment in research. Conclusions : First, access to medicines is perceived to be a major problem in India by all stakeholders, but affordability is just one factor. Second, stakeholders despite considerable support for the idea of the HIF, there are major concerns about scaleability, generalisability and impact on access to medicines. Third, the HIF and other novel drug-related health policies can afford to be more radical, e.g. working outside the existing intellectual property rights regime, targeting generic as well as branded drugs, or extending to research and development. Further innovations in access to medicines must involve country-specific key stakeholders in order to increase the likelihood of their success.